The biology of the red-billed oxpecker, buphagus erythrorhynchus (Stanley, 1814), in the Kruger National Park - Skinner, J.D. (John Dawson), 1932- (University of Pretoria, 2024)
Dissertation (MSc (Zoology))--University of Pretoria, 1976.